Design and analysis of flying u a V drone for sanitization purpose. (2022) - Mohan Jena, Santosh; Mahendra Sant, Somesh; Mishra, Ruby; Nayak, Santosh K; Nayak, Smaranika
Abstract: Drones are unmanned aerial vehicles that can perform a variety of tasks and can be employed in any sector. The major focus of this work is to show how drones/UAVs may combat the issues faced by COVID-19. With constructive qualitative research, this work is structured to provide insights into theory techniques. Using solid work Drones model is created and using Ansys static and explicit dynamic analysis are done. The fundamental contribution of this paper is to design a drone for sanitization and screening. This research will be extremely beneficial to people in this pandemic situation. [copyright information to be updated in production process]